Courage and fear a primer - Fox, Wesley L. (Potomac Books, Inc., 2007)
"I have only two men out of my company and twenty out of some other company. We need support, but it is almost suicide to try to get it here as we are swept by machine gun fire and a constant barrage is on us. I have no one on my left and only a few on my right. I will hold." First Lt. Clifton B.